Social Participation and Disability among Children from Underserved Immigrant and Nonimmigrant Households. Issue 4 (2nd October 2015) - Mirza, Mansha Parven; Kim, Yoonsang; Stoffel, Ashley; Carroll, Theresa; Magaña, Sandra
ABSTRACT: The population of immigrant children in the United States has increased dramatically. Little is known about how immigrant children, especially those with disabilities, fare on outcomes relevant to occupational therapy such as participation in home, school, and community activities. Using secondary data from the Making Connections survey, we compared social participation outcomes and predictors for children with/without disabilities from underserved immigrant and nonimmigrant households in a sample of 2, 295 children aged 3 to 17 years. We found that social participation rates differed significantly for children based on their disability and immigrant status and were lowest for immigrant children with disabilities. Several contextual factors were found to be associated with social participation of immigrant children, such as health insurance coverage, household education, household connectedness with the neighborhood, and access to computers and the Internet. Implications of these findings for occupational therapy practice and research are discussed.